STAEPE – Seção Técnica de Apoio ao Ensino, Pesquisa e Extensão - Patim, Samuel Aparecido; Oliveira, Renato Gomes de; Tutumi, Maurício Hiromi; Silva, Patrick Santos Nogueira da; Mendes, Reinaldo Inácio (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Samuel Aparecido Patim